2020
DOI: 10.2147/dmso.s274315
|View full text |Cite
|
Sign up to set email alerts
|

<p>Network Pharmacology Combined with Transcriptional Analysis to Unveil the Biological Basis of Astaxanthin in Reducing the Oxidative Stress Induced by Diabetes Mellitus</p>

Abstract: Purpose Astaxanthin (Ast) has been reported to reduce oxidative stress induced by diabetes mellitus (DM). The aim of this research was to give a systematic overview of the biological basis for this process. Methods Ast-targeted proteins were collected from the BATMAN database, Comparative Toxicogenomics Database, and STITCH database. Putative DM-related protein targets were collected from the GeneCards database. A DM-rat model was then built with streptozotocin (STZ) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Interestingly, recent work has shown that the carotenoid astaxanthin reduces oxidative stress in a streptozotocin-induced diabetes model combined with high sugar and high fat. Of 120 targeted proteins and more than 13,000 diabetes mellitus targets, network analysis combined with transcriptional analysis identified NQO1 as one of the 3 key targets together with Col5A1 and Notch 2 responsible for the intersecting networks leading to astaxanthin-induced decreases in oxidative stress and reduced insulin resistance [ 248 ].
Fig.
…”
Section: Relevance Of Nqo1 To Disease Statesmentioning
confidence: 99%
“…Interestingly, recent work has shown that the carotenoid astaxanthin reduces oxidative stress in a streptozotocin-induced diabetes model combined with high sugar and high fat. Of 120 targeted proteins and more than 13,000 diabetes mellitus targets, network analysis combined with transcriptional analysis identified NQO1 as one of the 3 key targets together with Col5A1 and Notch 2 responsible for the intersecting networks leading to astaxanthin-induced decreases in oxidative stress and reduced insulin resistance [ 248 ].
Fig.
…”
Section: Relevance Of Nqo1 To Disease Statesmentioning
confidence: 99%
“…COL5A1 encodes an alpha chain for one of the low abundance fibrillar collagens. Previous work revealed that Col5A1, Nqo1, and Notch2 modulated by Ast may promote insulin-releasing balance, relieve insulin resistance, and maintain normal size in marginal-zone B cells [42]. Besides, diseases associated with COL5A1 gene/protein from the curated CTD Gene-Disease Associations dataset suggested the potential association between COL5A1 and diabetes mellitus with a standardized value of 1.24401 [43].…”
Section: Discussionmentioning
confidence: 99%
“…The ability of ATX to decrease inflammatory processes as well as reduce free radicals has been extensively reported in scientific literature. In our present review we found several studies in animals and humans where ATX had remarkable results in enzymes activity such as SOD [31,32,33] , GPx [27,34] , transcription factor signaling proteins such as AMPK [33] , control of inflammatory processes by inhibiting NF-kβ [35] , TNF-α [36,37] among others. These markers appeared four or more times in published in vivo works found in this review.…”
Section: Astaxanthin As Antioxidant and Antiinflammatorymentioning
confidence: 99%
“…These markers appeared four or more times in published in vivo works found in this review. We could observe that ATX can control the mechanisms of apoptosis in some diseases, such as dementia [33] , non-alcoholic hepatic steatosis [37] , type 2 diabetes [34] , glaucoma [38,39] , myocardial mitochondrial dysfunction [40] , myocardial injury [41,42] traumatic brain injury [33] , muscular dystrophy [43] , pancreatitis [44] and among many others. These mechanisms in most cases are associated with the control of NF-kB, TNF-a and consequently caspase-3.…”
Section: Astaxanthin As Antioxidant and Antiinflammatorymentioning
confidence: 99%
See 1 more Smart Citation